Global SUMOylome Adjustments in Basal Defenses of Arabidopsis thaliana Involve Complex Interplay Between SMALL-UBIQUITIN LIKE MODIFIERs and the Negative Immune Regulator SUPPRESSOR OF rps4-RLD1 - Kasera, Mritunjay; Ingole, Kishor D.; Rampuria, Sakshi; Walia, Yashika; Gassmann, Walter; Bhattacharjee, Saikat (Frontiers in Cell and Developmental Biology, 2021)
Steady-state SUMOylome of a plant is adjusted locally during developmental transitions, and more globally during stress exposures. We recently reported that basal immunity in Arabidopsis thaliana against Pseudomonas syringae pv tomato strain DC3000 (PstDC3000) is associated with strong enhancements in the net SUMOylome. Transcriptional upregulations of SUMO conjugases, suppression of de-conjugases, and increased SUMO translations accounted for this enhanced SUMOylation. Antagonistic roles of SUMO1/2 and SUMO3 isoforms further fine-tuned the SUMOylome adjustments thus impacting defense amplitudes and immune outcomes. Loss-of-function of SUPPRESSOR OF rps4-RLD1 (SRFR1), a previously reported negative regulator of basal defenses, also caused constitutive increments in global SUMO-conjugates through similar modes. These suggest that SRFR1 plays a pivotal role in maintenance of SUMOylation homeostasis and its dynamic changes during immune elicitations. Here we demonstrate that SRFR1 degradation kinetically precedes and likely provides the salicylic acid (SA) elevations necessary for the SUMOylome increments in basal defenses. We show that SRFR1 is not only a SUMOylation substrate, but also interacts in planta with both SUMO1 and SUMO3. In sum1 or sum3 mutants, SRFR1 stabilities are reduced albeit by different modes. Whereas a srfr1 sum1 combination is lethal, the srfr1 sum3 plants retain developmental defects and enhanced immunity of the srfr1 parent. Together with increasing evidences of SUMOs self-regulating biochemical efficiencies of SUMOylation-machinery, we present their impositions on SRFR1 expression that in turn counter-modulates the SUMOylome. Overall, our investigations reveal multi-faceted dynamics of regulated SUMOylome changes via SRFR1 in defense-developmental balance.